Facile and single-step entrapment of chloramphenicol in ZIF-8 and evaluation of its performance in killing infectious bacteria with high loading content and controlled release of the drug. Issue 10 (23rd February 2022) - Soltani, Sajjad; Akhbari, Kamran
Abstract : CLN@ZIF-8 was prepared by trapping chloramphenicol during ZIF-8 synthesis with high DLC and DLE. It showed H2 O2 -sensitive controlled release with higher drug release under the simulated infectious conditions and short-time antibacterial activity. Abstract : Mutations in infectious bacteria and reduced drug efficacy have forced researchers to test new systems that combine carriers and drugs to improve performance. Here, CLN@ZIF-8 nanoparticles were synthesized by simple single-step entrapment of chloramphenicol (CLN) in zeolitic imidazolate framework-8 (ZIF-8). Chloramphenicol is a widely used antibiotic and ZIF-8 is a MOF (metal–organic framework) with proven good properties as a carrier. In this route, a high drug loading content (DLC) of 32.58 ± 2.65% and a drug loading efficiency (DLE) of 56.80 ± 6.68% were obtained. In a new and practical approach, drug release was evaluated under conditions similar to infectious environments containing higher concentrations of H2 O2 and controlled release was achieved. Phosphate buffer played a decisive role in the destruction of the structure and release of the drug. The antibacterial activity was also measured by viable cell count assay and the results showed that CLN@ZIF-8 had a favorable efficacy in a short time. The structure of the compounds was also characterized using a variety of instrumental techniques.